URBAN ASPECTS OF DESIGN AND MANAGEMENT ON TERRITORIES OF BUFFER ZONES OF WORLD CULTURAL HERITAGE OBJECTS UNESCO - Korotun , Iryna; Popovych , Yevhenii (Collection of scientific papers «ΛΌГOΣ», 2022)
The authors consider modern approaches and experience in managing the territories of existing and potential World Heritage sites and their buffer zones through the prism of practical experience in creating and using buffer zones and the theoretical platform of this activity, including recommendations in international declarations, conventions and UNESCO guidelines.